Startegi Pemasaran Pada Kind Ichi Pie’n Cake Kota Bengkulu - Puspita sari, Indah; Afriani, Sulisti; Yanti, Rina Trisna (Journal of Management, Economic, and Accounting, 2022)
The purpose of this study was to determine the marketing strategy carried out by Kind Ichi Pie'n Cake in Bengkulu City. This study uses the method of analysis of Internal Factor Evaluation (IFE) and External Factor Evaluation by selecting consumers who come as respondents.Based on the results of the calculation of external internal factors, the total score for the internal strategy factor is 2.76 and the total external score is 2.44. From the results of this study, Bengkulu City's Kind Ichi Pie'n Cake is located in cell 4 using a strategy stability . This strategy shows that the company is in a stable condition, where the company focuses on existing business units by improving weaknesses and building company advantages